Burden and Prevention of Adverse Cardiac Events in Patients with Concomitant Chronic Heart Failure and Coronary Artery Disease: A Literature Review. Issue 3 (June 2016) - Lavoie, Louis; Khoury, Hanane; Welner, Sharon; Briere, Jean‐Baptiste
Summary: Background: Chronic heart failure (HF) or coronary artery disease (CAD) confers risk for thromboembolism and secondary adverse cardiac events (ACEs) (e.g., mortality, myocardial infarction, and stroke). When HF and CAD occur concomitantly, ACE risk is reported to be elevated. We investigated ACEs, their epidemiology, and the resulting burden among patients with concomitant HF and CAD through a structured review of recent literature. Antithrombotic treatment for ACE prevention was assessed. Methods: Pertinent databases (PubMed, other) were searched for relevant articles published from January 2004 to March 2015. Data collected included ACE incidence, healthcare resource use, costs, change in quality of life attributed to ACEs, and treatment practice for prevention of ACEs in patients with concomitant HF and CAD. Results: Mortality rates for patients with both HF and CAD ranged from 4.9–12.3% at 30 days to 13.7–86% for periods between 9.9 months and 10 years. Incidence of ACEs among HF patients with CAD is, respectively, at least 82% and 15% higher than for patients without HF or without CAD, except for stroke investigated in two studies. All‐cause and HF‐related hospitalization is the main driver of the economic burden in patients with HF, the majority of whom had CAD origin. Despite high prevalence of ischemic complications, there is limited evidence to support the use of warfarin‐type antithrombotics among HF patients. Conclusion: This study confirms that patients with concomitant HF and CAD are at elevated risk for ACEs and suggests the need for effective new antithrombotic treatments to further decrease ischemic complication rates in this population.